Midwives' knowledge of maternal and child health services during the Covid-19 pandemic in the province of Aceh - Sari, Yuni; Nurbaiti, Nurbaiti (Journal of Midwifery and Nursing, 2024)
Background. Coronavirus disease (Covid-19) is a global public health problem and is of great concern because of its potential to cause death and morbidity, particularly among vulnerable groups, including children, the elderly, people with co-morbidities, and health care workers. The risk of health workers spreading the disease is so high that it is critical that they remain knowledgeable about the COVID-19 pandemic and adhere to the service standards established by the Ministry of Health. This study was conducted to determine the factors associated with midwives' knowledge of maternal and child health services during COVD-19. Methods. The study sample consisted of 260 health workers (midwives) in Aceh Province who were members of the professional organization IBI in 2021. A questionnaire was used to measure health workers' knowledge of MCH services. Results. The statistical test results show that there is no significant relationship between age, length of employment, and knowledge of MCH service during the pandemic (p = 0.251). There is also no relationship between working hours and Middan's knowledge of MCH. Conclusion. The general public, including health workers, has very little knowledge about the transmission, symptoms, prevention, and control of the disease. Midwives are expected to have good knowledge and behaviors regarding infection prevention and the use of personal protective equipment (PPE) in the care of pregnant women, childbirth, newborns, and emergency complications. However, this study shows that the general public has very little information about the disease, especially in the provision of maternal health services.